Pandemonium : saving Europe - Middelaar, Luuk van, 1973- (Agenda Publishing, 2021)
"Over the past decade the European Union has faced threats to its currency, borders and unity. Covid-19, which began its inexorable spread across Europe in February 2020, is the latest crisis to test the Union's resilience. Luuk van Middelaar's compelling analysis of the EU's response to the pandemic details how events and decisions unfolded, how crisis solutions were improvised in a situation of deep uncertainty, and the lessons it must learn if it is to continue to protect its citizens. As member states shut their borders and scrambled for supplies, the European Union at first appeared irrelevant. But once shaken from its torpor by a public cry for help, the EU has coordinated a formidable response to the chaos, including an unprecedented level of financial assistance. This reaction, argues van Middelaar, demonstrates the Union's enduring strength and how it has learnt to deal with real world events. Indeed, the EU's response to the pandemic reveals how far it has come on its journey from regulatory body to geopolitical actor. The pandemic highlighted that Europe's next challenge will most likely come from its uneasy position between a strategically assertive China and a more self-centred United States. Facing this will require a greater political will than that mustered in the health emergency. To become a true power among powers, Van Middelaar contends, Europe must give firmer political shape to its own historical and cultural identity. Pandemonium cements Luuk van Middelaar's position as one of the most insightful commentators on EU politics. His powerful analysis will be welcomed by anyone seeking to understand Europe's dynamics and changing geopolitical role."--